2015
DOI: 10.1186/s12974-015-0295-7
|View full text |Cite|
|
Sign up to set email alerts
|

The role of PPAR activation during the systemic response to brain injury

Abstract: BackgroundFenofibrate, a PPAR-α activator, has shown promising results as a neuroprotective therapy, with proposed anti-inflammatory and anti-oxidant effects. However, it displays poor blood-brain barrier permeability leading to some ambiguity over its mechanism of action. Experimentally induced brain injury has been shown to elicit a hepatic acute phase response that modulates leukocyte recruitment to the injured brain. Here, we sought to discover whether one effect of fenofibrate might include the suppressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 56 publications
0
22
0
Order By: Relevance
“…Additionally, treatment with fenofibrate before stroke reduces the expression of ICAM-1 and VCAM-1, reduces adherent leukocytes, infiltrating neutrophils and regulates oxidative stress in the brain (Deplanque et al 2003; Ouk et al 2014a). Pre-treatment with fenofibrate also reduces neutrophils and gene expression of CXCL10, CXCL1 and SAA-1 in the liver after stroke (Losey et al 2015). PPARα agonist, WY14643, exhibits a similar reduction of adhesion molecule expression, oxidative stress and iNOS expression when used as a pretreatment to stroke (Collino et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, treatment with fenofibrate before stroke reduces the expression of ICAM-1 and VCAM-1, reduces adherent leukocytes, infiltrating neutrophils and regulates oxidative stress in the brain (Deplanque et al 2003; Ouk et al 2014a). Pre-treatment with fenofibrate also reduces neutrophils and gene expression of CXCL10, CXCL1 and SAA-1 in the liver after stroke (Losey et al 2015). PPARα agonist, WY14643, exhibits a similar reduction of adhesion molecule expression, oxidative stress and iNOS expression when used as a pretreatment to stroke (Collino et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…PPARα agonist improves stroke outcome by reducing adhesion molecule expression in the brain and, thereby, limiting early neutrophil infiltration, reducing inflammatory factors, regulating oxidative stress, and increasing cerebral blood flow (Deplanque et al, 2003; Collino et al, 2006; Guo et al, 2010; Ouk et al, 2013, 2014; Losey et al, 2015). However, PPARα agonists did not have the same protective effect in female mice subjected to MCAO (Dotson et al, 2016b).…”
Section: Translation Of Therapies To Both Sexesmentioning
confidence: 99%
“…Moreover, studies have found that cleaved caspase-3 activity increased gradually within 24 hours in the infarct core after transient MCAo; but the activity was overall lower in the nonperfused core after permanent occlusion, suggesting that caspase-3 activity depends on reperfusion by the fact that free radicals generated during reperfusion (6,14,18). So at our study, we demonstrated the ischemia-reperfusion MCAo rat model to observe the cleaved caspase-3 association with ischemic infarct volume.…”
Section: Middle Cerebral Artery Occlusion (Mcao)mentioning
confidence: 48%
“…Previous data showed that the post-ischemic activation of NF-κβ dependent genes has a key modulation on proinflammatory and proapoptotic study showed that pretreatment with fenofibrate improved the penumbral cerebral blood flow during MCAo (17). Recently, Losey et al observed that a 14-day fenofibrate pre-treatment decreased reactant production, infarct volume, and neutrophil recruitment to the brain and liver, which is a hallmark of the acute phase response (14).…”
Section: Effect Of Fenofibrate On Body Weightmentioning
confidence: 99%
See 1 more Smart Citation